WAYS OF EARLY DETECTION AND PREVENTION OF HYPERTENSION (American Journal of Interdisciplinary Research and Development, 2025)
Hypertension is one of the leading causes of the highest incidence and mortality worldwide today. Consistently higher than normal blood pressure leads to severe complications such as diseases of the cardiovascular system, stroke, heart failure and kidney damage. Therefore, early detection of hypertension, identification of risk factors and taking preventive measures are of great importance in maintaining human health. The article discusses ways to detect hypertension at an early stage, that is, monitoring constant blood pressure, measuring at home, undergoing a medical examination and determining the genetic predisposition. It also highlights the role of the main risk factors for the disease — overweight, poor diet, inactivity, stress, and an unhealthy lifestyle. For the prevention of hypertension, the need to form a healthy lifestyle, give up harmful habits, limit salt consumption, increase physical activity and control the psychological state, are emphasized. At the same time, increased preventive work among the population and timely consultation of health workers play an important role in preventing the development of hypertension.